The substantial first impact of bottom fishing on rare biodiversity hotspots: a dilemma for evidence-based conservation. - Robert Cook (Public Library of Science (PLoS), 2013)
This study describes the impact of the first passage of two types of bottom-towed fishing gear on rare protected shellfish-reefs formed by the horse mussel Modiolus modiolus (L.). One of the study sites was trawled and the other was scallop-dredged. Divers collected HD video imagery of epifauna from quadrats at the two study sites and directed infaunal samples from one site. The total number of epifaunal organisms was significantly reduced following a single pass of a trawl (90%) or scallop dredge (59%), as was the diversity of the associated community and the total number of M. modiolus at the trawled site. At both sites declines in anthozoans, hydrozoans, bivalves, echinoderms and ascidians accounted for most of the change. A year later, no recovery was evident at the trawled site and significantly fewer infaunal taxa (polychaetes, malacostracans, bivalves and ophuroids) were recorded in the trawl track. The severity of the two types of impact reflected the undisturbed status of the habitats compared to previous studies. As a 'priority habitat' the nature of the impacts described on M. modiolus communities are important to the development of conservation management policy and indicators of condition in Marine Protected Areas (EU Habitats Directive) as well as indicators of 'Good Environmental Status' under the European Union Marine Strategy Framework Directive. Conservation managers are under pressure to support decisions with good quality evidence. Elsewhere, indirect studies have shown declines of M. modiolus biogenic communities in fishing grounds. However, given the protected status of the rare habitat, premeditated demonstration of direct impact is unethical or illegal in Marine Protected Areas. This study therefore provides a unique opportunity to investigate the impact from fishing gear whilst at the same time reflecting on the dilemma of evidence-based conservation management.